Analisis Nilai Pendidikan Karakter Tokoh Utama dalam Novel Yang Telah Lama Pergi Karya Tere Liye - Adinda Oktavia Rahmadhany; Abdul Malik; Musliha Musliha; Isnaini Leo Shanty; Legi Elfitra; Dody Irawan (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to uncover the character education values reflected in the main character in Tere Liye's novel Yang Sudah Lama Pergi (The Long Gone). The focus of the study is to analyze how these character values are expressed through dialogue, actions, and the character development of the main character throughout the story. The approach used is descriptive qualitative with content analysis method, where the researcher acts as a key instrument supported by analysis guidelines and data coding sheets. Data collection techniques were carried out through in-depth reading of the novel three times, accompanied by note-taking and listening to the text to identify various aspects of the main character that are relevant to the character education values. The results show a comprehensive representation of 13 character education values in the main character. Religious values are reflected through the character's deep reflection on life and divinity, while honesty and discipline appear in the consistency of the character's thought patterns and actions. The analysis reveals that hard work and creativity are important pillars that drive conflict resolution in the story. Furthermore, the main character's curiosity drives narrative development, while national spirit is reflected in how the character interacts with diverse social environments. The findings indicate that a positive reception of others' achievements is a key character in building social relationships. The main character's ability to communicate, maintain peace, and demonstrate empathy represents the values of friendship and social care. The character's literacy patterns depicted through reading habits also enrich the learning aspects of the story. Responsibility as a central value is seen in various complex moral decision-making processes. This research has theoretical implications for literary studies by presenting a comprehensive analytical framework for character education, as well as practical implications for the world of education.